2023
DOI: 10.1245/s10434-023-13542-z
|View full text |Cite
|
Sign up to set email alerts
|

Fertility-Sparing Treatment for Early-Stage Cervical Cancer ≥ 2 cm: Can One Still Effectively Become a Mother? A Systematic Review of Fertility Outcomes

Carlo Ronsini,
M. C. Solazzo,
R. Molitierno
et al.

Abstract: Background Fertility-sparing treatments (FSTs) have played a crucial role in the management of early-stage cervical cancer (ECC); however, there is currently no standard of care for women with ECC ≥ 2 cm who wish to preserve their fertility. The current orientation of the scientific community comprises upfront surgical techniques and neoadjuvant chemotherapy (NACT) followed by minor surgery such us conization. However these approaches are not standardized. This systematic review aimed to collect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…According to the latest studies, the size of the primary tumor is a factor with a strong impact on survival [ 53 , 54 ]. In our study, this parameter did also appear to be statistically significant, despite the small number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to the latest studies, the size of the primary tumor is a factor with a strong impact on survival [ 53 , 54 ]. In our study, this parameter did also appear to be statistically significant, despite the small number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Its use has been mainly adopted as a means that will help reduce the extent of the procedure, which will concurrently help achieve better pregnancy rates. A recent systematic review that summarized evidence from 352 patients reported indeed that the use of NACT accompanied by less radical surgery considerably increased pregnancy rates and birth rates compared to standard fertility-sparing treatment with radical hysterectomy [ 39 ]. Survival rates were not, however, reported in this study.…”
Section: Early-stage Disease Challengesmentioning
confidence: 99%